A legal will document from Mameluke era (26 Ramadan 784 AH / 10 December 1382 AD) - Jazea, Mubarak Ashwi (Journal of Humanities & Social Sciences, 2022)
This research deals with a topic in the study of one of the distinctive Mameluke documents in the field of legal wills, which highlighted the nature of its formulation in that period. It also showed several aspects of the nature of people’s lives in the city of Nablus. The documents become an important source which we draw information that absent in those main sources. The study relied on the analytical method, after collecting the legal will information. As well as the information related to the study through sources and history references, to be analyzed and studied. The study reached several results: the prevalence of writing legal wills among the majority of the people at Mameluke period. It indicated the good manners of the testator and his honesty in mentioning debts. The research mentioned rare information about the various nature of the life of the people of Nablus. Finally, the calligrapher wrote the phrases in succession, without commas. It is the style of writing Mameluke documents to prevent forgery and fraud. I recommend to take care of researchers who interested of historical documents, to clarify historical facts well. Also, to overcome all difficulties which they always face it.